Role of Vitamin D Supplementation on Patients of Severe COPD to Reduce Exacerbations - Rahman, Md Habibur; Rouf, Md Abdur; Ahmad, Md Mohiuddin; Islam, Md Sayedul; Razzaque , S M Abdur; Anam, Md Khairul; Saha, Nihar Ranjan; Mondal, Prottush Kumar; Nasrin, Shamima; Iqbal, Mohammad Ashif; et al. (Chest & Heart Journal, 2023)
Background: Vitamin D deficiency is prevalent among patients with chronic obstructive pulmonary disease (COPD) and comes to be more frequent with increased disease severity. Low serum 25-hydroxyvitamin D (25-[OH]D) levels have been associated with lower FEV1, impaired immunologic control and increased airway inflammation which causes frequent exacerbations of COPD patients. Aims: To evaluate the role of vitamin D supplementation on patients of severe COPD to reduce exacerbations. Materials & Methods: This study was prospective observational study conducted at the Department of Respiratory Medicine in National Institute of Diseases of the Chest and Hospital from December, 2019 to March, 2021. Total 94 severe COPD patients were enrolled in this study, out of which 46 patients were taken in group A that include vitamin D deficiency (<20 ng/ml) group and 48 in group B that include vitamin D insufficiency (20-30 ng/ml) group. Results: Mean vitamin D level – initial (25.1±2.7 vs 10.9±3.8 ng/ml), at 3rd month (39.4±3.9 vs 32.5±3.2 ng/ml) and at 9th month (34.0±4.5 vs 22.7±4.9 ng/ml) were significantly (p<0.05) higher in group B than group A. Mean vitamin D level - at 9th month were statistically significant (p<0.05) within the group A and group B compare with initially. At 3rd month and at 9th month exacerbation were significantly higher in group A than group B. Conclusion: We concluded that vitamin D level was significantly increased at nine month in both group A and group B respectively. In both group, exacerbation was significantly reduce at nine month follow up than initially. So early supplementation of Vitamin D in exacerbation of severe COPD patients can reduce number of further exacerbation. Chest Heart J. 2021; 45(1) : 26-30